MicroRNA-489-3p attenuates neuropathic allodynia by regulating oncoprotein DEK/TET1-dependent epigenetic modification in the dorsal horn. (1st June 2022) - Lai, Cheng-Yuan; Hsieh, Ming-Chun; Yeh, Chou-Ming; Yang, Po-Sheng; Cheng, Jen-Kun; Wang, Hsueh-Hsiao; Lin, Kuan-Hung; Nie, Siao-Tong; Lin, Tzer-Bin; Peng, Hsien-Yu
Abstract: Originally characterized as an oncoprotein overexpressed in many forms of cancer that participates in numerous cellular pathways, DEK has since been well described regarding the regulation of epigenetic markers and transcription factors in neurons. However, its role in neuropathic allodynia processes remain elusive and intriguingly complex. Here, we show that DEK, which is induced in spinal dorsal horn neurons after spinal nerve ligation (SNL), is regulated by miR-489-3p. Moreover, SNL-induced decrease in miR-489-3p expression increased the expression of DEK, which recruited TET1 to the promoter fragments of the Bdnf, Grm5, and Stat3 genes, thereby enhancing their transcription in the dorsal horn. Remarkably, these effects were also induced by intrathecally administering naïve animals with miR-489-3p inhibitor, which could be inhibited by knockdown of TET1 siRNA or DEK siRNA. Conversely, delivery of intrathecal miR-489-3p-mimic into SNL rats attenuated allodynia behavior and reversed protein expression coupled to the promoter segments in the dorsal horn. Thus, a spinal miR-489-3p/DEK/TET1 transcriptional axis may contribute to neuropathic allodynia. These results may provide a new target for treating neuropathic allodynia. Highlights: Nerve injury upregulates spinal DEK to drive neuropathic pain. Nerve injury-decreased miR-489-3p induces expression of DEK that recruited Tet1 to the promoter fragments of nociceptive genes in the dorsal horn. Intrathecal miR-489-3p-mimic reversal of pain behavior and reversed protein expressions and coupling to the promoter segments in the dorsal horn. This signaling is also induced by intrathecally administering naïve rats with miR-489-3p inhibitor, which could be inhibited by Tet1 siRNA or DEK siRNA.